Pengujian Daya Hambat Ekstrak Bubuk Temu Putih (Curcuma zedoaria (Berg.) Roscoe) Terhadap Aspergillus flavus - Brahmasari, Hana Kusuma; Darmayanti, Luh Putu Trisna; Suparthana, I Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 3 (2023): Jurnal ITEPADO - 10.24843/itepa.2023.v12.i03.p18, 2023)
This study aimed to determine the extract of concentration of white turmeric powder in inhibiting the growth of the fungus A. flavus and to determine of active substances contained in the white turmeric powder. The parameters bioactive compounds observed total phenol contains, total flavonoids contains, and curcumin contains. White turmeric powder was extracted using 96% ethanol. The extraction method used is maceration. This study used a Completely Randomized Design with several concentrations of concentrated extract of white turmeric powder consisting of 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 100%. All treatments were repeated twice to obtain 20 experimental units and the data obtained were analyzed by descriptive analysis and interpreted with tables and figures.. The test results showed that the concentrated extract of white turmeric powder was not effect to inhibit the growth of the fungus A. flavus. The results showed that white turmeric powder contained phenol 576.225 mg GAE/100g, flavonoids 1.090.65 mg/100g, and curcumin 14.35 mg CE/100g.